2016
DOI: 10.1055/s-0036-1592339
|View full text |Cite
|
Sign up to set email alerts
|

Innovative Multimodal Physical Therapy Reduces Incidence of Repeat Manipulation under Anesthesia in Post–Total Knee Arthroplasty Patients Who Had an Initial Manipulation under Anesthesia

Abstract: Manipulation under anesthesia (MUA) is performed for knee stiffness following a total knee arthroplasty (TKA) when nonoperative treatments fail. It is important to develop an optimal outpatient physical therapy protocol following an MUA, to avoid a repeat procedure. The purpose of this study was to evaluate and compare: (1) range of motion and (2) the rate of repeat MUA in patients who either underwent innovative multimodal physical therapy (IMMPT) or standard-of-care physical therapy (standard) following an M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
(25 reference statements)
0
2
0
Order By: Relevance
“…The study results are consistent with the conclusion of Mc Cormack [27] who revealed significant pain reduction with the improvement of the lower limb function in the patient with high hamstring tendinopathy. The finding of Chughtai [28] proved a significant gain in knee joint ROM in patient who underwent Astym therapy compared with standardized physical therapy program following total knee arthroplasty. Chughtai [28] and Paker [29] proved that the joint pain and ROM might be related to effects of Astym on the biomechanical properties of the injured tissues with enhancement of blood flow and possible angiogenesis in the vicinity of these tissues Patients with Ant-CECS might have transient or permanent lowgrade foot drop as a result of the weakness of dorsiflexors with or without paresthesia on the dorsum of the foot.…”
Section: Discussionmentioning
confidence: 92%
“…The study results are consistent with the conclusion of Mc Cormack [27] who revealed significant pain reduction with the improvement of the lower limb function in the patient with high hamstring tendinopathy. The finding of Chughtai [28] proved a significant gain in knee joint ROM in patient who underwent Astym therapy compared with standardized physical therapy program following total knee arthroplasty. Chughtai [28] and Paker [29] proved that the joint pain and ROM might be related to effects of Astym on the biomechanical properties of the injured tissues with enhancement of blood flow and possible angiogenesis in the vicinity of these tissues Patients with Ant-CECS might have transient or permanent lowgrade foot drop as a result of the weakness of dorsiflexors with or without paresthesia on the dorsum of the foot.…”
Section: Discussionmentioning
confidence: 92%
“…After undergoing treatment with Astym therapy for a mean of 17 sessions, there were improvements in flexion deficit (70º to 105º, P≤0.001), flexion contracture (15º to 3º, P≤0.001), and the Knee Society objective (57 to 80 points, P<0.0001) and function scores (54 to 80 points, P=0.0003). In another study (24), they evaluated 57 patients (57 knees) who had a mean age of 59 years (range, 32 to 81 years) who underwent TKA followed by MUA either underwent standard of care physical therapy (n=35) or innovative multimodal physical therapy (IMMPT), which included Astym therapy (n=22). At the 6-month evaluation, the IMMPT group did not have any repeat MUAs, but the standard of care group had 7 repeat MUAs (P=0.025), and the IMMPT group had better knee flexion compared to the standard of care group (116º vs. 106º, P=0.005).…”
Section: Kneementioning
confidence: 99%